PERAN STRATEGIS KEJAKSAAN DALAM PEMULIHAN EKONOMI NASIONAL MASA PANDEMI COVID-19 (Studi Kasus Pada Kejaksaan Tinggi Sulawesi Utara) - Afada, Abik (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
This study aims to strengthen the main tasks and functions of the Prosecutor's Office in order to oversee the recovery of the National Economy so as to be able to oversee national economic growth and be able to encourage and oversee the implementation of refocusing activities and budget reallocation to accelerate co-19 countermeasures. This study uses qualitative research with field observation and interview methods. North Sulawesi High Prosecutors Office always improves performance in efforts to reform the bureaucracy and Corruption-Free Region (WBK) so that it has a strategic role in national economic recovery.